Diary of a Wimpy Kid: The Long Haul - Kinney, Jeff (New York Amulet Books, 2014)
The Heffley family road trip starts off full of promise, then quickly takes several wrong turns--with everything from a fender bender to crazed seagulls--but even the worst road trip can turn into an adventure, and this is one the Heffleys will not soon forget.
Keywords: Automobile travel -- Juvenile fiction; Vacations -- Juvenile fiction; Families -- Juvenile fiction; Diaries -- Juvenile fiction; Family life -- Fiction; Road fiction; Humorous fiction; Fiction